PENGEMBANGAN BUKU KOSAKATA BAKU DI KELAS III SDN 2 SUWAWA KABUPATEN BONE BOLANGO - Dwi Erninda Puspita; Wiwy T. Pulukadang; Rusmin Husain; Fidyawati Monoarfa; Rustam I. Husain (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a standard vocabulary book as a learning medium for Grade III students at SDN 2 Suwawa and to assess the level of feasibility and practicality of this medium. The study employed a Research and Development (R&D) model utilizing the ADDIE approach, which encompasses the stages of analysis, design, development, implementation, and evaluation. The results of the analysis showed that students still experienced difficulties in mastering standard vocabulary and lacked attractive learning media; therefore, teaching materials suitable for the characteristics of elementary school students were needed. The developed product was a vocabulary book containing a collection of standard words accompanied by simple illustrations and example sentences. Product validation was conducted by four experts: a media expert, a language and content expert, a subject-matter expert, and a teacher, who served as the user expert. The validation results showed that the media expert provided a feasibility percentage of 75% (Feasible), the language and content expert 90% (Very Feasible), the subject- matter expert 87% (Very Feasible), and the user expert 100% (Very Feasible). Overall, the average feasibility reached 88% and was categorized as Very Feasible. In the practicality test, the researcher used a teacher observation sheet and obtained a percentage of 100%, while the student observation sheet obtained a percentage of 97.5% with the category "very practical." The trial with Grade III students also yielded very positive responses, students felt helped in understanding standard vocabulary and showed increased interest in the learning process. Thus, the developed standard vocabulary book is considered feasible and effective for use as a learning medium to improve the mastery of standard vocabulary among Grade III students at SDN 2 Suwawa.